A free-piston Stirling cryocooler using metal diaphragms. (December 2016) - Caughley, Alan; Sellier, Mathieu; Gschwendtner, Michael; Tucker, Alan
Highlights: Metal diaphragms to suspend the displacer of a free-piston Stirling cryocooler. Successful proof of concept prototype testing. Sage model prediction and validation with prototype. Abstract: A novel concept for a free-piston Stirling cryocooler has been proposed. The concept uses a pair of metal diaphragms to seal and suspend the displacer of a free-piston Stirling cryocooler. The diaphragms allow the displacer to move without rubbing or moving seals, potentially resulting in a long-life mechanism. When coupled to a metal diaphragm pressure wave generator, the system produces a complete Stirling cryocooler with no rubbing parts in the working gas space. Initial modelling of this concept using the Sage modelling tool indicates the potential for a useful cryocooler. A proof-of-concept prototype was constructed and achieved cryogenic temperatures. A second prototype was designed and constructed using the experience gained from the first. The prototype produced 29 W of cooling at 77 K and reached a no-load temperature of 56 K. Sage predicted the macroscopic behaviour of the prototype well but did not provide sufficient insights to improve performance significantly. This paper presents details of the development, modelling and testing of the proof-of-concept prototype and a second, improved prototype.